Application of polymer split grouting technology in earthen dam: Diffusion law and applicability. (10th March 2023) - Hao, Yanjie; Guo, Chengchao; Shi, Mingsheng; Wang, Fuming; Xia, Yangyang; Wang, Chaojie
Highlights: A visualized numerical model of polymer directional fracturing grouting considering the time-varying viscosity and swelling characteristics of slurry was established. The diffusion mechanism of directional fracturing of polymer under the influence of grouting hole type, grouting amount, grouting rate, soil elastic modulus and cohesion was revealed. A small fracturing pore-forming device was developed, and the polymer directional splitting grouting technology was applied to the practice of slope anti-seepage reinforcement engineering. High density electrical method and DCP penetration test were used to evaluate the anti-seepage reinforcement effect. Abstract: The split grouting method can play a very good anti-seepage and reinforcement effect for some soil dykes that are not compacted or have hidden dangers such as leakage channels, soft layers, cracks, biological caves and so on. The polymer oriented splitting grouting technology is a new measure with high efficiency, minimally invasive and no need for maintenance. The research literature on the application of polymer oriented splitting grouting technology in the field of seepage prevention and reinforcement of soil dyke is quite limited. In this paper, the law of directional splitting and diffusion of non-aqueous polymer grouting materials is studied. In view of the difficulty in simulating the dynamic process of directional splitting grouting of polymer by existing numerical methods, a visual model of directional splitting grouting process of polymer was established by using discrete element particle flow program (PFC2D) considering the influence of the expansion characteristics and viscosity of polymer materials with time, and the field test was carried out. The results show that the polymer directional splitting grouting process can be divided into four stages: filling, extrusion, split-extrusion cycle and final extrusion, and the final shape of slurry veins is "spindle". In addition, through the numerical simulation of PFC2D, it is found that the diffusion shape of polymer grouting materials is affected by the shape of grouting hole, the amount of grouting, the rate of grouting, the elastic modulus of soil and the cohesion of soil, and can play a role in filling and compacting soil to a certain extent. Finally, the application of polymer oriented splitting grouting is carried out for the leakage danger of a canal embankment project. Through the in-situ standard penetration test and high density electrical detection, it is proved that the polymer oriented splitting grouting technology can quickly stop the water and compacted the soil, and further improve the stability and integrity of the soil embankment.